Bone Injury and Repair Trigger Central and Peripheral NPY Neuronal Pathways - Alves,CJ (2016)
Bone repair is a specialized type of wound repair controlled by complex multi-factorial events. The nervous system is recognized as one of the key regulators of bone mass, thereby suggesting a role for neuronal pathways in bone homeostasis. However, in the context of bone injury and repair, little is known on the interplay between the nervous system and bone. Here, we addressed the neuropeptide Y (NPY) neuronal arm during the initial stages of bone repair encompassing the inflammatory response and ossification phases in femoral-defect mouse model. Spatial and temporal analysis of transcriptional and protein levels of NPY and its receptors, Y1R and Y2R, reported to be involved in bone homeostasis, was performed in bone, dorsal root ganglia (DRG) and hypothalamus after femoral injury. The results showed that NPY system activity is increased in a time- and space-dependent manner during bone repair. Y1R expression was trigged in both bone and DRG throughout the inflammatory phase, while a Y2R response was restricted to the hypothalamus and at a later stage, during the ossification step. Our results provide new insights into the involvement of NPY neuronal pathways in bone repair.